Analysis of a Single-Unit System with Weibull Failure and Repair densities Subject to Server Failure - Kumar, Ashish; Saini, Monika (Malaysian Journal of Science, 2016)
The main concentration in the present paper is to analyze a single- unit system using the concepts of inspection, degradation, preventive maintenance, and server failure. A single repair facility inspect the original and degraded unit upon failure to check the feasibility of repair. The repair facility may fail during maintenance, repair and inspection and undergoes for treatment with Weibull probability density function. The unit after repair becomes degraded. Switch devices are perfect. All random variables like repair time, failure time, inspection time and treatment rate are independent and statistically independent. For the analysis of the system various measures of system effectiveness are obtained by using semi-Markov processes and regenerative point technique. With the help of numerical and graphical results for MTSF, availability and profit functions it is concluded that present system is more reliable, available and profitable, when random variables have less vale of shape parameters. Keywords: System, Availability, Inspection, Degradation and Preventive Maintenance